Improving PRESENT lightweight algorithms - AlDabbagh, Sufyan Salim Mahmood; Alshaikhli, Imad Fakhri Taha (2013)
Lightweight block cipher algorithms are vital for constrained environment. Substitution box (S-box) is the essential constituent of many lightweight block cipher algorithms and it is the only nonlinear part. It is proficient to create confusion in the plaintext during the process of encryption. In this research, a new way of key dependent S-box is proposed by choosing one S-box out of 16 good S-boxes. Preliminary analysis of linear and differential cryptanalysis is showing that the proposed algo